KONTRIBUSI TENAGA KERJA WANITA PADA USAHA EMPING MELINJO TERHADAP PENDAPATAN KELUARGA (Studi Kasus di Desa Sukomangli Kecamatan Reban Kabupaten Batang) - Muhamad Nurul Amin; Suprapti Supardi; Shofia Nur Awami (MEDIAGRO, 2016)
The aims of this research are to know the average working hour of women labor in emping melinjo business, to know how much women labor contribution emping melinjo business to the family income and to know the factors that influencing the income of those women labor. The basic method used in this research are descriptive method. Respondents consisting of 40 women labor for the research were selected by purposive sampling. The data consisting of primary and secondary data. They are collected by interviewing, observating and recording. The research result shows that the women labor average working hour in emping melinjo business is 9 hours/day or 37.5 percent. The contribution of women labor in emping melinjo business to the family income was 61.71%. The R2 value was obtained using multiple linier regression model of 0,984 meaning that the contribution of independent variable (age, education, working hour, business experience, number of emping melinjo produced, number of family members and sales system) to the variation women labor income in the emping melinjo business in Sukomangli Village Reban District Batang Regency of 98.4 percent while 1.6 percent remaining is affected by other variables excluded from the model. The result of F-test and t-test shows that the number of emping melinjo produced and sales system variable are significantly affect to the women labor income contribution. While age, education, working hour, business experience and number of family members variable are not significantly affect to the women labor contribution.   Keywords: contribution, emping melinjo, women labor